TANGGUNG JAWAB ANAK TERHADAP ORANG TUA LANJUT USIA (LANSIA) DI DESA KAARUYAN KECAMATAN MANANGGU KABUPATEN BOALEMO - Dolot Alhasni Bakung; Fence M Wantu; Weny A Dungga; Dian Ekawaty Ismail; Zamroni Abdussamad; Suwitno Y Imran; Mohamad Hidayat Muhtar; Julius T Mandjo (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2022)
Along with the time that continues to turn where previously children who were still toddlers were taken care of by their parents until they moved to the village and got a job and were busy to have a partner and offspring and their own lives, on the other hand the parents who used to raise them have now entered old age which should be the child's obligation to take care of parents at that time. The dilemma that occurs between the obligation to care for wives and children and work with caring for parents when they enter old age or old age. Responding to the phenomenon that occurs related to the child's obligation to choose parents when entering old age. So the service team from the Faculty of Law, Goronalo State University conducted counseling in a number of villages which basically had a number of problems related to this, including Kaaruyaan Village, Paguyaman District, Boalemo Regency, Gorontalo Province. The problems raised in this service include the background of children taking care of their own elderly parents at home and children who entrust elderly parents in nursing homes. Legal review of the responsibilities of children who entrust their parents in nursing homes. This research method uses qualitative methods and discussions in counseling, where the research was carried out in the Kaaruyaan Village area. The subjects of counseling are children who care for and children who entrust elderly parents (Elderly) in Nursing Homes. Observation, interviews and documentation. Extension results. The background of children choosing to entrust elderly parents in the orphanage is triggered by a number of things including work, obstacles in communication between family and parents, incompatibility between the wife / husband and parents in the house. While the background of children chooses to take care of their own parents at home, facilitate communication with parents, control physical health, guarantee the needs and needs of parents daily to apply forms of love and affection to parents.